Recommendations for the use of COVID-19 vaccines in patients with immune-mediated kidney diseases - Kronbichler, Andreas; Anders, Hans-Joachim; Fernandez-Juárez, Gema Maria; Floege, Jürgen; Goumenos, Dimitrios; Segelmark, Mårten; Tesar, Vladimir; Turkmen, Kultigin; van Kooten, Cees; Bruchfeld, Annette; Immunonephrology Working Group of the ERA-EDTA (European Renal Association – European Dialysis, Transplant Association) (Nephrology, dialysis, transplantation, 2021)
Coronavirus Disease 19 (COVID-19) vaccine platforms are becoming available and are the most promising strategy to curb the spread of SARS-CoV-2 infections. However, numerous uncertainties exist regarding the pros and cons of vaccination, especially in patients with (immune-mediated) kidney diseases on immunosuppressive drugs. Here, members of the Immunonephrology Working Group (IWG) of the European Renal Association-European Dialysis and Transplant Association (ERA-EDTA) discuss thirteen frequently-asked questions regarding safety and efficacy of the most promising vaccine candidates. Post-marketing surveillance should be performed to estimate the rate of vaccine response (humoral and cellular) of different vaccine platforms, and surveillance of disease activity following administration of COVID-19 vaccines. Some of the candidates induce signaling pathways which also promote autoimmune kidney diseases, e.g. type I interferons in systemic lupus erythematosus. Efficacy estimates would thus far favor the use of selected COVID-19 vaccines, such as BNT162b2, mRNA-1273 or Gam-COVID-Vac. Humoral immune response after vaccination should be monitored using appropriate assays. Even in the absence of neutralizing antibodies patients might be protected by a sufficient cellular immune response capable to reduce severity of COVID-19. A reduced vaccine response after the use of CD20-depleting agents is anticipated, and it is particularly important to discuss strategies to improve vaccine response with these patients. Distancing and shielding measures remain important as not all vaccines fully protect from coronavirus infection. In-depth information about the most pressing vaccine questions is essential to reduce vaccine hesitancy of patients.
Keywords: immunity; glomerulonephritis; immune response; COVID-19; vaccine